Model synthesis of energy compressors - Kuzmitchev, I.K.; Melezhyk, P.M.; Pazynin, V.L.; Sirenko, K.Yu.; Sirenko, Yu.K.; Shafalyuk, O.S.; Velychko, L.G. (Інститут радіофізики і електроніки ім. А.Я. Усикова НАН України, 2008)
A complete electrodynamic model and a synthesis algorithm of energy compressors have been developed for the first time. The theoretical problems have been solved that occur when constructing these structures on the basis of two connected in series axiallysymmetrical open waveguide resonators “storage + switch”.